SUBJECTIVE ECONOMIC WELL-BEING OF BANK EMOK CUSTOMERS' FAMILIES: AN ANALYSIS OF DEBT BEHAVIOR, LIFESTYLE, ECONOMIC PRESSURE, AND FAMILY FINANCES: Kesejahteraan Ekonomi Subjektif Keluarga Nasabah Bank Emok: Analisis Perilaku Berhutang, Gaya Hidup, Tekanan Ekonomi, Dan Keuangan Keluarga - Sunarti, Euis; Kusumaningrum, Woro Dwi; Zammi, Mahfud (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2024)
The utilization of money is not optimal, making the family's financial condition inefficient, which is why the family decides to get into debt at the Bank Emok. This study aims to analyze the influence of the family's debt behavior, lifestyle, economic pressure, and financial conditions (literacy and management) on the subjective economic well-being of Bank Emok customers in Bogor City. The research used a cross-sectional study design involving 150 families of Bank Emok customers selected by simple random sampling. The research instrument has adequate reliability and validity. The results of the analysis show that there are Bank Emok customers who are not categorized as poor. Many client families do not fulfill 12 years of primary education. Loans range from 2-16 million, with an average weekly installment of 138 thousand. As many as 26,7 percent of families fall into the category of high economic pressure, which is characterized by the difficulty of families in fulfilling food, education, and life skills. The results of the regression test show that the subjective economic welfare of families is positively influenced by lifestyle, financial literacy, financial management, number of dependents, length of wife's education, and length of loan. The analyzed model contributed 27,2 percent to the subjective economic well-being of families. Families are advised to start making financial plans and implement saving habits to be used in emergencies to improve the subjective economic well-being of the family.